Metacognitive Process in English Writing - Ika Lestari; Berlin Sibarani; Didik Santoso (LINGUISTIK TERAPAN, 2014)
This research deals with metacognitive process in English writing to the students of STIP-AP Medan. The objectives of the research were to find out what metacognitive processes occur to the students’ English writing, to describe how does the metacognitive process occur in English writing of STIP-AP students and to find out the reason why the metacognitive process occur in that way. This research conducted by applying descriptive qualitative design. The subject of this research was the university students of STIP-AP Medan in the third semester. The data were obtained from the think aloud protocol and interview. The data collected were analyzed by applying Miles and Huberman’s model. The findings would like to see metacognitive process that occur in English writing. Almost students could not write in English very well, it was signed from their awareness that their metacognition didn’t aware. So that, there were something wrong in their metacognition when they wrote something in English. Finally, by knowing the process metacognition in English writing such as planning, monitoring, and evaluating in writing, students could be aware to write English text very well.   Keywords: Causes; Metacognitive, Writing